Effect of acid and base catalyzed hydrolysis on the yield of phenolics and antioxidant activity of extracts from germinated brown rice (GBR) - Sani, Ismaila Muhammad; Iqbal, Shahid; Chan, Kim Wei; Ismail, Maznah (MDPI, 2012)
The influence of both acidic and basic hydrolysis on the yield, total phenolic content and antioxidative capacity of methanolic extract of germinated brown rice (GBR) was studied. Total phenolic content (TPC), total flavonoid content (TFC), 2,2′-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging, 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid (ABTS) radical cation scavenging, and ferric reducing antioxidant power (FRAP) tests were used for the measurement of antioxidant ability. There was a significant difference (p < 0.05) in the TPC and DPPH radical scavenging assay results when comparing neutral with acidic and basic catalysed hydrolysis. The yield of the crude extract was slightly higher in acidic hydrolysis than in basic hydrolysis (p > 0.05). The TPC and TFC were highest in acidic hydrolysis. A significant correlation was observed between ABTS radical cation scavenging and FRAP. The antioxidant activity measured using DPPH radical scavenging assay showed high activity in acidic hydrolysis, while the ABTS radical cationscavenging activity and FRAP showed the highest values in basic hydrolysis. The samples were further evaluated using HPLC to determine the individual phenolic concentrations in different hydrolytic media contributing to the antioxidant effects. This study revealed that acidic and basic hydrolysis can improve the yield, phenolic content, and antioxidant activity of germinated brown rice.